2008
DOI: 10.1007/s11431-008-6008-z
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the crop transpiration using an optimality-based approach

Abstract: Evapotranspiration constitutes more than 80% of the long-term water balance in Northern China. In this area, crop transpiration due to large areas of agriculture and irrigation is responsible for the majority of evapotranspiration. A model for crop transpiration is therefore essential for estimating the agricultural water consumption and understanding its feedback to the environment. However, most existing hydrological models usually calculate transpiration by relying on parameter calibration against local obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
0
9
0
1
Order By: Relevance
“…Caylor et al [66] indicated that, in a region with limited water, the optimization mechanism of vegetation-hydrological interaction was to maximize the utilization of water resources and minimize water stress. In addition, Wang et al [67], Pauwels et al [68], and Lei et al [69] carried out related work.…”
Section: A Description Of the Interaction Between Vegetation And Hydmentioning
confidence: 99%
“…Caylor et al [66] indicated that, in a region with limited water, the optimization mechanism of vegetation-hydrological interaction was to maximize the utilization of water resources and minimize water stress. In addition, Wang et al [67], Pauwels et al [68], and Lei et al [69] carried out related work.…”
Section: A Description Of the Interaction Between Vegetation And Hydmentioning
confidence: 99%
“…However, this is also the most challenging issue in ET studies. Nevertheless, there have been numerous attempts on this issue, such as the thermodynamic entropy theory (Bobylev et al 2001), machine learning approach (Yang et al 2006;Sudheer et al 2002) and ecosystem optimality theory (Lei et al 2008). …”
Section: Current Issuesmentioning
confidence: 99%
“…During the past decade, various models have been developed to partition available energy at the soil-plantatmosphere interface and to simulate mass or energy movement in the soil. Examples include those developed by Wilson et al (2003), Lee and Mahrt (2004), Lei et al (2008) and Krobel et al (2010). A common SPAC model usually includes two parts, the below-ground part (soil) and the above-ground part.…”
Section: Advantages Of the Hybrid Dual-source Modelmentioning
confidence: 99%
“…The functional soil map is the result of a RS classification of the same Landsat 7 data; the five functional soil classes and three sub-classes as in Table 1. (Hundecha and Bárdossy 2004), (b) mechanistic representation of the major functionality in the water cycle (Tietjen et al 2009), (c) data-driven look-up table referencing (Güntner and Bronstert 2004), and (d) optimality-based approaches (Lei et al 2008, Schymanski 2008. Jackson et al (2009) underpin the strong link between hydrology and ecology and point out that in agricultural systems this link is very simplified and degrees of freedom are reduced.…”
Section: Eco-hydrological Model Options and Selectionmentioning
confidence: 99%